2019
DOI: 10.1097/md.0000000000017076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical fitness on colorectal tumor development in patients with familial adenomatous polyposis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A previous study similarly reported that a high CRF reduced the incidence of colorectal polyps in men by 31.3% [12]. Nakamura et al [21] reported that colorectal polyps exhibited an inverse relationship with CRF. Studies on CRF and polyps are still few compared to cancer studies, and some studies showed that the presence of association differs according to age and sex.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study similarly reported that a high CRF reduced the incidence of colorectal polyps in men by 31.3% [12]. Nakamura et al [21] reported that colorectal polyps exhibited an inverse relationship with CRF. Studies on CRF and polyps are still few compared to cancer studies, and some studies showed that the presence of association differs according to age and sex.…”
Section: Discussionmentioning
confidence: 95%
“…The incidence is relatively higher in populations over 50 years old and relatively lower in those under 50 years old [2]. According to reports from developed countries such as the United States and Australia, due to the popularity of CRC screening in recent years, the incidence of CRC in the United States has declined [3]. The incidence of CRC in males and females has decreased by 2.8% and 2.2% annually on average, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of CRC in young adults is increasing. The incidence of CRC among young males and females in the 20-49 age group is increased by 1.5% and 1.6%, respectively per year in the United States [3].…”
Section: Introductionmentioning
confidence: 99%
“…Besides genetic factors such as family history and inherited syndromes, inflammatory bowel disease may increase the incidence of CRC [ 2 , 3 , 4 ]. In addition, lifestyle factors, such as dietary habits and lack of physical activity, may also contribute to an increased risk of CRC [ 5 , 6 , 7 ]. Although combinations of surgical resection and therapies have been potentially applied to patients depending on the stage and the subtype of cancer, treatment options in this malignancy still remain suboptimal.…”
Section: Introductionmentioning
confidence: 99%